Efficacy of micafungin in empirical therapy of deep mycosis in surgically ill patients - Okamoto, Kohji; Katsuki, Takefumi; Tamura, Toshihisa; Kanemitsu, Shuichi; Minagawa, Noritaka; Torigoe, Takayuki; Shibao, Kazunori; Higure, Aiichirou; Yamaguchi, Koji (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2012)
Micafungin (MCFG), an echinocandin antifungal agent, exhibits antifungal activity against Candida albicans and non-albicans Candida. The fungicidal activity of MCFG against clinical isolates of Candida species was investigated, and the clinical efficacy of MCFG in therapy of deep mycosis in surgery was studied using the AKOTT algorithm. The minimum inhibitory concentration and minimum fungicidal concentration values of fluconazole were ≤0.06–4 and >64μg/ml, respectively, for each strain, whereas these values of MCFG were 0.008–0.5 and 0.016–1μg/ml, suggesting that MCFG provided superior fungicidal ability against Candida albicans and non-albicans Candida. The subjects were separated into two groups: group A consisted of 20 subjects with both persisting fever refractory to broad-spectrum antibiotics and positive reaction to β-d-glucan test, and group B consisted of 20 subjects with either of those conditions. The overall response was evaluated as “effective” in 17 patients (85%) and 20 patients (100%) in groups A and B, respectively. In total, response was evaluated as “effective” in 37 patients (92.5%) and “ineffective” in 3 patients (7.5%). These findings suggest that MCFG administration should be used as empirical therapy for deep mycosis in surgically ill patients as it was shown to be an effective antifungal drug lacking serious adverse effects.